Analisis Dan Perancangan Sistem Informasi Pemesanan Tiket Berbasis Web Pada CV.Bima Sakti Mandiri - Arlina, Lisa; Setiawan Asegaff; Herry Mulyono (LPPM Universitas Dinamika Bangsa, 2024)
Technological advances enable companies to increase operational efficiency, expand market reach, and improve customer experience. However, CV. Bima Sakti Mandiri in Jambi is still facing problems in the offline-based ticket ordering process, such as errors in assigning seat numbers, inaccurate departure information, and customer difficulties in obtaining reschedule information. This research aims to analyze problems at CV. Bima Sakti Mandiri and designed a web-based ticket booking information system as a solution to these problems. This research uses the UML modeling method, which includes Use Case Diagrams, Class Diagrams, and Activity Diagrams, as well as flowcharts to design the system. The research results show that CV. Bima Sakti Mandiri experienced problems in ordering tickets, such as incorrect information from officers and rescheduling management. The information system designed produces a prototype that makes it easier for users to order tickets, view real-time seat availability, departure schedules, reschedules, ticket prices, order history, e-wallet payment methods, manage customer data and reports. The results of the analysis and design of this system can be a solution to the obstacles faced as well as a reference for developing a web-based ticket ordering information system. To increase security, CV. Bima Sakti Mandiri must implement SSL encryption, the latest security protocols, firewalls, two-factor authentication (2FA), and a strict privacy policy. Researchers further suggest adding features such as real-time tracking services, reviews and ratings, as well as developing a system using mobile-based technology.